ANALISIS KESULITAN GURU MATEMATIKA DALAM PEMBELAJARAN DARING DI ANGKOLA JULU - Rapika Hafsyah Nasution; Muhammad Syahril Harahap; Nunik Ardiana (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The purpose of this study is to know the difficulties of mathematic teachers in learning online in Covid – 19 periodin AngkolaJulu. The approach of the research used qualitative descriptive with 3 mathematic teachers. Questionnaire and interview were used in collecting the data and triangulation was used in checking the data validity. Analysis of the data includes data reduction, data presentation, and taking conclusion. The result of the research shows the difficulties of mathematics teachers in using various media, conducting ask and answer, overcome the students problem in mastering subject, in giving comprehension subject, applying the goal of learning, difficulties in operating the computer, awaken students’ motivation, difficulties to know students’ mastering of subject, difficulties in accessing internet, and difficulties in arranging the time.